Potential of use tropical fruit co-products in the elaboration of new food products (Research, Society and Development, 2023)
Agroindustry is one of the sectors that most produces organic waste, which is usually discarded in the environment incorrectly, leading to environmental pollution. Therefore, the use of agro-industrial co-products can contribute to reducing environmental impacts, since they are rich in bioactive compounds that act in health promotion and can be used for the development of food products with added value, representing a promising area of scientific and technological development. The objective of this study was to identify the potential of tropical fruit co-products and their use in the formulation of new food products. The literature review was performed using the electronic databases Science Direct, Scielo and PubMed, as well as Google Scholar. Complete articles published during the period 2016-2022 in Portuguese and/or English and related in a relevant and objective way to the proposed theme were included. The results showed that these co-products can be used to formulate new products such as flour, biscuits, bread, cookies, sweets, have low production cost and high nutritional and functional value. In this way, there are several benefits in the use of agro-industrial co-products from tropical fruits, being a promising alternative for innovation in the food industry, promoting health and well-being and stimulating the circular economy in a way that industry and society benefit, contributing to the development sustainability and to combat food insecurity.